Utilization of Water Hyacinth to Reduce Sedimentation and Evapotranspiration in the Saguling Reservoir by PT PLN Indonesia Power Saguling POMU - Alfira Salsabila; Sofiyah; Taufan Kurniawan (GoAcademica Research & Publishing, 2023)
Water hyacinth is an aquatic plant with wide leaves and fast growth in conditions of many nutrients, causing them to thrive in the waters of the Saguling Reservoir, West Bandung. Dead water hyacinth will settle to the bottom of the waters, resulting in an increase in reservoir sedimentation. In addition, the wide leaves and roots that absorb water make water hyacinth increase reservoir evapotranspiration, namely water loss due to evaporation and transpiration. Therefore, PT PLN Indonesia Power Saguling POMU initiated a program to utilize water hyacinth by local communities to process it into various products, such as handicrafts, fuel, animal feed, and compost. This study used secondary data analysis. Geospatial analysis through digitizing satellite imagery was used to measure the trend of water hyacinth numbers in the Saguling Reservoir with the utilization of water hyacinth. Then, a sedimentation analysis was carried out using utilized water hyacinth numbers approach, while evapotranspiration analysis was carried out using water hyacinth distribution numbers approach and meteorological data. The water hyacinth utilization program by PT PLN Indonesia Power Saguling POMU in the Saguling Reservoir from 2013 to July 2023 effectively reduced 8,382,572 kg of water hyacinths, reduced sediment in the reservoir by 829,875 kg, reduced sedimentation rate by 0.09%, and played a role in reducing the evapotranspiration of the reservoir, thus increasing the life of the reservoir.